Peer Teaching as a Simulation for Communicative Classroom English Rehearsal - Atik Rokhayani; Agung Dwi Nurcahyo; Dwi Rukmini; Ahmad Sofwan (Soegijapranata Catholic University, 2017)
One of the professional competences that should be owned by English teachers is classroom English skill since they have to deliver instructions in various classroom context. Consequently, it becomes a challenge for teacher training and education institutions to prepare their student teachers with good English speaking skills for instructional purposes. Student teachers usually have to complete a teaching internship program for one semester at school so as to engage them in a real situation of teaching experience. In that period of time, they will have to use appropriate classroom language when giving instructions to their students. Therefore, student teachers should be provided enough opportinuties for practicing their classroom English skill. In Indonesian English Education Department there is a compulsory course named ‘micro teaching class’ that should be attended by student teachers before they have a teaching internship program at school. This study aims at describing how peer teaching is practiced by the students of the English Education Department of Universitas Muria Kudus as a simulation activity to use classroom English in delivering classroom’s instruction. The study will explore to what extent this simulation can help student teachers improve their communicative competence in classroom instructional process.